2023
DOI: 10.14218/jcth.2023.00067
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches to Inhibition of HBsAg Expression from cccDNA and Chromosomal Integrants: A Review

Ahmed H. Abdelwahed,
Brent D. Heineman,
George Y. Wu

Abstract: Hepatitis B virus (HBV) is a widely prevalent liver infection that can cause acute or chronic hepatitis. Although current treatment modalities are highly effective in the suppression of viral levels, they cannot eliminate the virus or achieve definitive cure. This is a consequence of the complex nature of HBV-host interactions. Major challenges to achieving sustained viral suppression include the presence of a high viral burden from the HBV DNA and hepatitis B surface antigen (HBsAg), the presence of reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…However, these drug candidates are still in preclinical or early clinical stages of development. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these drug candidates are still in preclinical or early clinical stages of development. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…However, these drug candidates are still in preclinical or early clinical stages of development. 45,46 In this study, we investigated the antiviral activity of dopamine, a small molecule compound. Our findings demonstrate that dopamine substantially reduced the level of HBV DNA, which was consistent with our previous study showing that dopamine reduced HBV DNA replication by inhibiting the binding of ε RNA with the HBV polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Abdelwahed et al. found that rs2069845 was associated with a reduced risk of CHB in a Saudi Arabian cohort ( 121 ).…”
Section: Relation Between Tlr Polymorphism and Severity Or Susceptibi...mentioning
confidence: 99%